EFEKTIVITAS MODEL PEMBELAJARAN TALKING CHIPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Darmawan Harefa (Universitas Nias Raya, 2023)
The aim of this research is to determine and describe improvements in the quality and cognitive learning outcomes of students. This research method is classroom action research with 2 cycles, namely: planning, action, observation and reflection. The research results showed that students were active in expressing opinions, learning to discuss, clarifying ideas and concepts of the material they were studying so that student learning outcomes from cycle 1 to cycle 2 were better. Conclusion: the talking chips learning model is effective for improving the quality of learning and students' cognitive learning outcomes, where each student gets the opportunity to make their contribution and listen to each other's views and thoughts. The suggestion put forward by researchers is that integrated science subject teachers should use the talking chips learning model in learning activities at school.